Umetna inteligenca - Stojan, Eva (Pravni letopis, 2021)
The article addresses the fundamental dilemmas concerning the status of artificially intelligent systems in civil law, considering their specific characteristics: autonomy, (in)transparency and learning ability. Special attention is given to the question of liability for damages in tort cases involving artificial intelligence and the proposal of granting it legal personhood. The victims are those most frequently affected by the legal gaps that the lack of regulation creates. Through the prism of European soft law and legal theory, the author critically discusses the appropriateness of adapting the current civil law framework and introducing new ones. By granting them legal personhood, artificially intelligent systems could be equalized with natural and juridical persons, thus possessing rights and bearing responsibilities. Alternatively, there is a possibility of introducing new concepts, such as "e-personhood" and adapting them to our needs. The goal of compensation, as one of the main purposes of tort law, can also be achieved by using the institutes of compulsory insurance and compensation funds.
Keywords: civilno pravo; obligacijska razmerja; odgovornost; odškodninska odgovornost; odškodninsko pravo; regulacija; tehnološke inovacije; umetna inteligenca; zakonodaja